Simulating e-garments dressed on personalised avatars - Dias, J. M. S.; Muiños González, D.; Gamito, M. N. (SIACG2002 - 1st lbero-American Symposium in Computer Graphics, 2022)
We present a general computational architecture that solves the problem of the production of physical-based virtual textiles and garments (so-called electronic garments or e-garments), applicable in internet-based electronic-commerce scenarios. We focus on the evaluation of their visual and mechanical precision, relative to the textile quality control procedures adopted by the industry. Our proposed architecture includes a client that authors an e-garment dressed onto a personalized avatar, establishing the boundary conditions of the mechanical system and, a server, that solves the equilibrium equations through time of such system, using optimized numerical procedures. The client inputs 2D cutting patterns from apparel CAD vendors, defines the seams between the CAD patterns, sets fabric material proprieties, loads a personalized avatar into a JD scene, places the patterns relative to the JD avatar, configures simulation parameters, and instructs the remote server to simulate the e-garment dressing process. We conclude with the validity of our new computational framework for modeling e-garments made of plain-woven fabrics and the applicability of the system in a more global internet-based electronic commerce solution for the online shopping of apparel and fashion goods.